PRIORITIES FOR INCREASING THE EXPORT CAPACITY OF ENTERPRISES - Mamadaliyev , Akmaljon (Универсальная индексная библиотека Центрально-Азиатского журнала междисциплинарных исследований и исследований управления, 2024)
This article focuses on the possibilities of exporting the products of the enterprises abroad and their effective use. In addition, scientific recommendations aimed at the liberalization of foreign exchange policy to increase the export potential of enterprises, improvement of export support by studying the experiences of advanced countries, identification of factors influencing the industry, and export support were developed